Hispanic Parent-Child Relationships and Communication on Substance Use and Sex in 4th-6th Graders - Matsuda, Yui; Lee, Jiye; Parra, Alexa; Thalasinos, Roxana D.; Laporte, Roberto Roman; Updegraff, Kimberly (International Journal of Mass Communication, 2025)
Background and Purpose: Parent-child communication is vital in preventing pre-adolescent health risk behaviors such as substance use and sex, yet little is known about these dynamics in Hispanic families. This study explored how Hispanic parents and their pre-adolescent children communicate about such risks. Methods: Using a qualitative descriptive design, researchers conducted focus groups and interviews with 24 Hispanic parents and 23 children (grades 4–6) from an afterschool program in the Southeastern U.S. Data were analyzed using conventional and directed content analysis. Results: Children expressed love and respect for their parents but were hesitant to discuss sensitive topics. Parents wanted to guide their children but struggled with timing conversations about sex, managing media use, and general parenting challenges. Mothers noted that fathers were often less involved in these discussions. Conclusions: Culturally and developmentally tailored interventions are needed to support Hispanic parents in addressing risk behaviors with their children.